2022
DOI: 10.1080/15592294.2022.2088464
|View full text |Cite
|
Sign up to set email alerts
|

Residential green space in association with the methylation status in a CpG site within the promoter region of the placental serotonin receptor HTR2A

Abstract: Green space exposure could influence cognition in adults and neurodevelopment in children, and is hypothesized to be partly driven by epigenetic modifications. However, it remains unknown whether some of these associations are already evident during foetal development. Developmental processes in the foetal brain and placenta are shaped by similar biological signals. Therefore, we hypothesize that green space exposure can modify epigenetic processes of cognition-related pathways in placental tissue, such as DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 68 publications
1
6
1
Order By: Relevance
“…In the same population here under study, in a targeted study, Dockx et al (2022) found green space associated with placental methylation of HTR2A, which was also among the cord blood DMRs we identified as linked with green space.…”
Section: Resultssupporting
confidence: 52%
See 2 more Smart Citations
“…In the same population here under study, in a targeted study, Dockx et al (2022) found green space associated with placental methylation of HTR2A, which was also among the cord blood DMRs we identified as linked with green space.…”
Section: Resultssupporting
confidence: 52%
“…Finally, we compared meta-EWASs results with associations previously reported in placenta ( Dockx et al, 2022 ), in children ( Lee et al, 2021 ) and in adult studies ( Jeong et al, 2022 ; Xu et al, 2021a ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prenatal greenspace exposure has been associated with reduced odds of autism spectrum disorder and healthier birth weights (16,17). Notably, maternal greenspace exposure has been shown to have a positive association with methylation status of HTR2A in placental tissue which has significant implications for serotonin and child neurodevelopment (18). Maternal prenatal stress results in hormone dysregulation and affects the epigenetic regulation of placental HPA axis (i.e., glucocorticoid) genes that can elevate susceptibility of psychopathology (19).…”
Section: Environment and The Epigenomementioning
confidence: 99%
“…This essential organ regulates nutrient and oxygen transfer and hormone and immune supply, and may act as a barrier to environmental exposures, playing a key role in foetal growth and development (Griffiths & Campbell, 2015;Mortillo & Marsit, 2022). To date, only a candidate gene study has explored the association between green space and placental DNAm, where the methylation status of the serotonin receptor HTR2A was positively associated with pregnancy green space exposure (Dockx et al, 2022). Thus, it is important to explore the association between maternal green space exposure during pregnancy and DNAm in placenta not only in specific genes but also on a genome-wide scale in relatively large samples sizes.…”
Section: Introductionmentioning
confidence: 99%